Efficacy of topical steroid therapy for phimosis treatment: a systematic review - Andika Rendy; Arry Rodjani; Irfan Wahyudi (DiscoverSys Inc., 2020)
Background: Circumcision is the gold standard in the management of phimosis cases. Nowadays, there is some basic science research that showed topical steroid might be used to decrease the morbidity of phimosis cases. This research aims to determine which management is more effective in treating phimosis by using a systematic evidence-based medicine approach.Methods: Literature searching was done to find journals that are deemed appropriate for these cases. We included 3 RCT studies in this review. Critical appraisal was conducted to determine the efficacy of topical steroid. We compared those two methods in managing cases of phimosis among children.Results: Topical steroids effectively cause the preputium skin be soft and comfortable to retract. In several cases, some patients had difficulty to get retracted. For these cases, circumcision is needed.Conclusion: Topical steroid is effective in reducing the phimosis signs and symptoms, especially in patients who are younger and less than 3 years old. Further study and meta-analysis should be conducted in Indonesia to determine the effectiveness of this therapy in Indonesia.